1990
DOI: 10.5271/sjweh.1796
|View full text |Cite
|
Sign up to set email alerts
|

Risk of neuropsychiatric disability among painters in the United States.

Abstract: BRACKBILL RM, MAIZLlSH N, FISCHBACH T. Risk of neuropsychiatricdisabilityamong painters in the United States. Scand J Work Environ Health 1990;16:182-8. Scandinavianstudieshave suggested that working with solvents is associated with chronic neuropsychiatric disease. In the United States the Social SecurityAdministration's records of white male recipients of disability compensation were used in a case-referentstudy on this topic. The cases were defined as men with anyone of 'several neuropsychiatric diseases, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…For suicide, there is some published evidence that painters have an increased rate of neuropsychiatric disorders. 25 In summary, the modest excesses of lung and bladder cancers that we have found among painters are consistent with an occupational aetiology and are consistent with the scientific literature. Confounding by smoking may play a part in these excesses, particularly for lung cancer which is highly related to smoking, but any such confounding is unlikely to completely explain these findings.…”
Section: Discussionsupporting
confidence: 89%
“…For suicide, there is some published evidence that painters have an increased rate of neuropsychiatric disorders. 25 In summary, the modest excesses of lung and bladder cancers that we have found among painters are consistent with an occupational aetiology and are consistent with the scientific literature. Confounding by smoking may play a part in these excesses, particularly for lung cancer which is highly related to smoking, but any such confounding is unlikely to completely explain these findings.…”
Section: Discussionsupporting
confidence: 89%
“…However, considering all of the disability pension studies and the study by Labrèche et al (1992), the combined evidence for such an effect is not consistent. Two disability pension studies showed no evidence of an increased risk of alcohol-related diagnoses among solvent-exposed workers (Lindström et al, 1984;van Vliet, 1989) and, in a third, the evidence was not very strong (Brackbill et al, 1990). Furthermore, no crosssectional study has reported interaction effects between alcohol consumption and solvent exposure.…”
Section: Psychiatric Morbidity Studiesmentioning
confidence: 99%
“…Nine studies, including six case-referent studies and three cohort studies, on neuropsychiatric disability related to solvent exposure have been published (Axelson et al, 1976;Olsen and Sabroe, 1980;Mikkelsen, 1980;Lindström et al, 1984;Gubéran et al, 1989;van Vliet et al, 1989;Brackbill et al, 1990;Riise and Moen, 1990;Lundberg et al, 1992). They query whether the exposure effects observed in cross-sectional studies may become chronic and disabling.…”
Section: Disability Pension Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Bleecker et al (1991) and Spurgeon et al (1992) found no indications of increased solvent-related symptoms in solvent-exposed subjects, while Morrow et al (2000) found increased incidences of anxiety and depressive disorders or depression in other solvent-exposed patients, and Condray et al (2000) report an increased prevalence of mood disorders among journeyman painters. Some studies have reported excessive risk for painters and other solvent-exposed workers of developing a psychiatric disorder leading to early retirement (Axelson et al 1976;Brackbill et al 1990, Hogstedt and Axelson 1986, Mikkelsen 1997. However, it remains unclear how exposure to organic solvents during the working life aVects general well-being later in life, after cessation of exposure.…”
Section: Introductionmentioning
confidence: 97%